Doripenem: A new carbapenem in clinical practice [Doripenem: Klinik uygulamada yeni bir karbapenem] - KORTEN, VOLKAN (DOC Design and Informatics Co. Ltd., 2010)
Doripenem is the newest addition to the carbapenems, the most active class of antibiotics against many resistant pathogens. This review focuses on the antimicrobial, pharmacological and clinical aspects of doripenem. Its spectrum of activity is similar to that of meropenem and imipenem. According to the Turkish data of comparative activity of carbapenem (COMPACT) study, doripenem inhibited 64% of Pseudomonas aeruginosa at MIC 2 μg/ml, whereas meropenem and imipenem inhibited 56.2%, and 48.2% of the isolates, respectively. Unlike imipenem or meropenem, doripenem is stable for 12 hours at room temperature and may be delivered safely as a 4-hour extended infusion. This practice of administration lengthens the duration of time that the concentration of doripenem remains above the MICs of less susceptible pathogens. Based on animal models, doripenem has less epileptogenic activity than imipenem. Doripenem has been approved for use in treatment of complicated intraabdominal infection, complicated urinary tract infection, hospital-acquired pneumonia, and ventilator-associated pneumonia that are caused by susceptible pathogens.
Keywords: Carbapenem; Doripenem; Pseudomonas aeruginosa